2015
DOI: 10.1111/aas.12673
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter‐based emergency medical services for a sparsely populated region: A study of 42,500 dispatches

Abstract: BackgroundThe Helicopter Emergency Medical Service (HEMS) in Norway is operated day and night, despite challenging geography and weather. In Western Norway, three ambulance helicopters, with a rapid response car as an alternative, cover close to 1 million inhabitants in an area of 45,000 km2. Our objective was to assess patterns of emergency medical problems and treatments in HEMS in a geographically large, but sparsely populated region.MethodsData from all HEMS dispatches during 2004–2013 were assessed retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 21 publications
11
51
0
Order By: Relevance
“…Figure 3 summarizes that a significant portion of the studies dealing with problems related to emergency medical services in order to contribute to decreased response time, resources, coverage and routes, for example, make use of simulation, algorithms and data analysis through descriptive statistics 24,25 . Data evaluation shows that the localities found, positioned mainly in Europe and North America, present a response time in accordance with what is expected for this type of service, having an estimated time of approximately 8 minutes according the WHO 2,[30][31][32][33] .…”
Section: ■ Resultssupporting
confidence: 74%
“…Figure 3 summarizes that a significant portion of the studies dealing with problems related to emergency medical services in order to contribute to decreased response time, resources, coverage and routes, for example, make use of simulation, algorithms and data analysis through descriptive statistics 24,25 . Data evaluation shows that the localities found, positioned mainly in Europe and North America, present a response time in accordance with what is expected for this type of service, having an estimated time of approximately 8 minutes according the WHO 2,[30][31][32][33] .…”
Section: ■ Resultssupporting
confidence: 74%
“…Previous studies 7,8 have shown a similar demographic of a higher proportion of road traffic collisions occurring by night and also assaults. These assault victims may suffer blunt or penetrating trauma that may require enhanced medical care.…”
Section: Discussionmentioning
confidence: 59%
“…Approximately 30% of all HEMS dispatches are cancelled on the basis of no longer being medically needed . Physician‐staffed mobile medical teams are dispatched with a deliberately low threshold in the Netherlands, resulting in 43.5% of the missions being aborted .…”
Section: Discussionmentioning
confidence: 99%
“…The municipalities are responsible for primary health care, including first responders and a comprehensive out‐of‐hours GP service; the regional health trusts are responsible for ground, boat, and air ambulances, as well as hospitals. The HEMS in our region was described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation